Comprehensive chromosomal aberrations in a case of a patient with TCF3-HLF-positive BCP-ALL - Monika Lejman; Monika Włodarczyk; Joanna Zawitkowska; Jerzy R. Kowalczyk (BMC, 2020)
Abstract Background The use of high-throughput analytical techniques has enabled the description of acute lymphoblastic leukaemia (ALL) subtypes. The TCF3-HLF translocation is a very rare rearrangement in ALL that is associated with an extremely poor prognosis. The TCF3-HLF fusion gene in the described case resulted in the fusion of the homeobox-related gene of TCF3 to the leucine zipper domain of HLF. The TCF3-HLF fusion gene product acts as a transcriptional factor leading to the dedifferentiation of mature B lymphocytes into an immature state (lymphoid stem cells). This process initiates the formation of pre-leukaemic cells. Due to the rarity of this chromosomal aberration, only a few cases have been described in the literature. The advantage of this work is the presentation of an interesting case of clonal evolution of cancer cells and the cumulative implications (diagnostic and prognostic) of the patient's genetic alterations. Case presentation This work presents a patient with diagnosed with TCF3-HLF-positive ALL. Moreover, the additional genetic alterations, which play a key role in the pathogenesis of ALL, were detected in this patient: deletion of a fragment from the long arm of chromosome 13 (13q12.2-q21.1) containing the RB1 gene, intragenic deletions within the PAX5 gene and NOTCH1 intragenic duplication. Conclusions A patient with coexistence of chromosomal alterations and the TCF3-HLF fusion has not yet been described. Identifying all these chromosomal aberrations at the time of diagnosis could be sufficient to determine the cumulative effects of the described deletions on the activity of other oncogenes or tumour suppressors, as well as on the clinical course of the disease. On the other hand, complex changes in the patient's karyotype and clonal evolution of cancer cells call into question the effectiveness of experimental therapy.